THE AUTOMODEL SOLUTIONS OF COMPLEX VALUED NONLINEAR DIFFERENTIAL EQUATION IN PARTIAL DERIVATIVES - Olga V. Novikova (Вестник Северо-Кавказского федерального университета)
The aim of this article is to find the automodel solutions of nonlinear equation in partial derivatives with the complex valued function. The system of equations, which equivalent to the observable model, is examined at the beginning of the article. The modification of the system to the type, which allows to get the automodel solutions, is shown. The author describes every step of the analysis in detail. As a result, he achieves his aim.